2014
DOI: 10.1055/s-0034-1390029
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Revision Arthroplasty for Su Type 3 Supracondylar Periprosthetic Knee Fractures

Abstract: Periprosthetic distal femoral fractures can present significant reconstructive challenges when associated with poor bone stock, comminution, or component loosening. Revision arthroplasty with stemmed components or distal femoral replacement arthroplasty often becomes necessary. This retrospective study reviewed the results of femoral revision arthroplasty in 16 knees with acute, extreme distal (Su type 3), supracondylar periprosthetic fractures using cemented, midlevel constrained implants. The mean patient ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The distal femoral replacement group did not have an increased complication rate; on the contrary, the recovery of patients was quicker with a shortened surgical time and decreased blood loss. Thakur et al [60] reported the results in 16 knees with acute Su type III, supracondylar periprosthetic fractures. All patients mentioned in their article returned to pre-fracture activity level.…”
Section: Revision Total Knee Replacementmentioning
confidence: 99%
“…The distal femoral replacement group did not have an increased complication rate; on the contrary, the recovery of patients was quicker with a shortened surgical time and decreased blood loss. Thakur et al [60] reported the results in 16 knees with acute Su type III, supracondylar periprosthetic fractures. All patients mentioned in their article returned to pre-fracture activity level.…”
Section: Revision Total Knee Replacementmentioning
confidence: 99%
“… 26 , 27 This may sometimes be a treatment option in cases where stability has been preserved between the bone and implant, and in Type 3 cases where bone stock is not of a sufficient amount and quality in the distal. 28 …”
Section: Discussionmentioning
confidence: 99%
“…10,21,32,36,37,39,41,46,47 The proportion of patients returning to preoperative mobility ranged from 37.5% to 95.2% in the DFLP group 10,33,38,39,42 and 27.3%-100.0% in the DFR group. 10,37,[39][40][41]47 Functional Outcomes Functional outcomes are reported in Table 3. The KSS ranged from 70.4 to 86.0 for DFLP knees [34][35][36]49,51 and from 67.2 to 86.0 for DFR knees.…”
Section: Clinical Outcomesmentioning
confidence: 98%
“…10,18,19,21, Seventeen studies reported on ORIF with DFLPs in 440 knees in 440 patients (12 retrospective studies 10,18,33,34,36,39,42,45,[49][50][51][52] and 5 case series 35,38,43,44,48 ). Eleven studies reported on DFR in 209 knees in 205 patients (9 retrospective studies 10,19,21,32,36,37,39,40,47 and 2 case series 41,46 ) (see Table, Supplemental Digital Content 2, http://links.lww.com/JOT/B368 for summarized study characteristics). The average age of DFLP knees ranged from 65.9 to 88.3 years, and the average age of DFR knees ranged from 71.0 to 84.8 years.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation